Steamed rice, or surfed? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In mid-September 2002, the International Rice Research Institute (IRRI) launched its Rice Knowledge Bank, modestly describing it as the world s repository of rice learning and knowledge. It is on the Internet and on CD-ROM. Its e-learning section...